Militarism in Environmental Disguise: The Greenwashing of an Overseas Military Base1. Issue 1 (11th March 2015) - Harris, Peter
Abstract : What is the relationship between militarized landscapes, especially overseas military bases, and the natural environment? Scholars have noticed that militarized spaces—permanent bases, demilitarized zones, live fire ranges, training areas, historical battlefields and so forth—are often accompanied by de facto nature reserves. Thus, the unparalleled seclusion that militarization imposes upon delineated geographic spaces can create safe havens for plants and animals that would otherwise suffer from human encroachment. Others retort that military activities cause severe damage to the natural environment. In this article, I problematize attempts to evaluate the environmental impact of militarized spaces in a way that divorces the natural environment from the broader web of social and political relations to which military activities belong. In particular, I argue that environmental issues often serve as "greenwash" to distract attention—lay, scholarly, and official—from the negative aspects of militarism, including instances of environmental degradation, the mistreatment of human subjects, and the perpetuation of colonial forms of government. To illustrate and buttress my argument, I present a detailed case study of the US military base on Diego Garcia in the British Indian Ocean Territory.